IMPLEMENTATION OF PHYSICAL FITNESS VISUAL BOARD TO ESTABLISH COMMUNITY PHYSICAL FITNESS LEVEL IN BATU LICIN COASTAL, SOUTH KALIMANTAN - Edwin Wahyu Dirgantoro; Lazuardy Akbar Fauzan (UNIB Press, 2021)
The coastal area is a space for humans to do activities. The area is a place for the community to carry out various sports and other physical activities. Every sport activity carried out regularly will affect the level of physical fitness. This study aims to determine the acceptance response of the physical fitness visual board and the effectiveness of the physical fitness visual board to determine the physical fitness level of the community. This research is a quantitative descriptive. The sample in this study was Batulicin coastal community as many as 50 people. In collecting data in this study, a survey method with test techniques was conducted. To determine the fitness level, the test used was the 2.4 km running test. To find out the public response to the use of physical fitness visual boards, questionnaires were distributed. The results of this study showed that the body mass index (BMI) was included in the ideal body category of 58%, the category of body fat was 16%, and the category of the thin body was 26%. The levels of physical fitness of the coastal community are 40% in good category, 40% in acceptable category, 16% in poor category, 2% for each very good category and very poor category. The acceptance response to the physical fitness visual board is in the very good category. A sample as much as 94% said it was very good. The effectiveness of using the physical fitness visual board to determine the level of physical fitness of the community is in the very good category. A sample of 94% stated very well.